PENGARUH POC KULIT NANAS DAN NPK ORGANIK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Ezra Prana Alta; Desrihastuti; T. Edy Sabli; Saripah Ulpah (UIR Press, 2025)
The decline in land area and the stagnation of cocoa production pose challenges for managing a sustainable cocoa production system, resulting in low plant productivity. One contributing factor is the use of suboptimal cultivation techniques, so improvements must begin at the nursery stage. The study aims to determine the interaction and main effects of Pineapple Peel POC and organic NPK on the growth of cocoa plant seedlings. The study was conducted at the Experimental Garden of the Faculty of Agriculture, Riau Islamic University, Pekanbaru, from May to August 2025. The study used a factorial Completely Randomized Design (CRD) with two factors. The first factor was Pineapple Peel POC, with four treatment levels: 0, 25, 50, and 75 ml/l of water. The second factor was organic NPK at four levels (0, 10, 14, and 18 g/plant). The parameters observed were cocoa plant height, number of leaves, stem diameter, total leaf area, and root volume. Observation data were analyzed for variance, and the BNJ test continued at the 5% level. Based on the results of the study, the interaction effect of pineapple peel POC and organic NPK was significant for cocoa plant height, number of leaves, stem diameter, total leaf area, and root volume. The best treatment was pineapple peel POC at 75 ml/l in water, with organic NPK at 18 g/plant. The main effect of pineapple peel POC was significant on all parameters, and the best treatment was pineapple peel POC at a concentration of 75 ml/l of water. The main effect of organic NPK was substantial across all parameters; the best treatment was 18 g/plant.